FACTORS AFFECTING FEMALE STUDENTS IN CHOOSING ENGINEERING AS AN ACADEMIC DEGREE AND PROFESSION IN GENDER-SEGREGATED SOCIETY IN SAUDI ARABIA - Shahd Alharazi; Noshaba Batool (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study had discussed factor of Saudi female student in chosen Engineering as an academic degree and profession in gender-segregated society of Saudi Arabia and attempt to explore motivational factors behind their decisions. The study purpose was understanding the Saudi female students who choose engineering as major even though the female student expected to face cultural issues or less job opportunities in the Saudi culture. The data collection was using quantitative method. The data were collected through anonymous survey included several statements about motivational factor and issues. The study targeted Saudi engineering students at universities in Jeddah especially EFFAT University used convenient sampling. The sample sizes were 50 females engineering students. The result showed intrinsic and social motives lead female student preferred engineering as a profession, their desire to understand engineering more and contribute in helping the society was enough for female students in pursued engineering studies in gender-segregated society. Moreover, future study had studied different possible way to encourage both government and society to improve female engineering image in support Saudi female students to choose engineering as career path